'Praise the Lord! We are a Musical Nation': The Welsh Working Classes and Religious Singing. Issue 3 (14th December 2020) - Barlow, Helen
Abstract : The title quotation from Under Milk Wood encapsulates a widely held belief in the innate musicality of the Welsh and its religious roots. These roots were put down deeply during the nineteenth century, in a huge expansion of choral and congregational singing across Wales and particularly in the industrial communities. This development has been described as 'a democratic popular choral culture rooted in the lives of ordinary people', and central to it was the cymanfa ganu, the mass hymn-singing festival. Choral and congregational singing, typified by the cymanfa ganu, underpinned the perception of Wales by the Welsh and by many non-Welsh people as 'the land of song'. Alongside this phenomenon ran the tradition of the plygain, a Welsh Christmas carol service. While the cymanfa developed in nonconformist chapels in the mid to late nineteenth century, and on a large – often massive – scale, the plygain is a tradition dating from a period much further back, when Welsh Christianity was Catholic; it belonged to agricultural workers rather than the industrial communities; and the singers sang in much smaller groups – often just twos or threes. This article describes the nature and origins of these contrasting traditions, and looks at the responses of listeners both Welsh and non-Welsh, and the extent to which they perceived these practices as expressive of a peculiarly Welsh identity. It also considers some of the problems of gathering evidence of working-class responses, and how far the sources give an insight into working-class listening experiences.